Analisis Pengaruh Merger Dan Kinerja Keuangan Terhadap Nilai Perusahaan: Studi Kasus Pada PT Gojek Tokopedia (GOTO) Tbk Tahun 2021 – 2023 - Cornellius Nathanael Hartanto; Muhammad Fata Aditya; Irvan Adetyatama Diono Putra; Endang Kartini Panggiarti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The research goal is to analyze the impact of merger which is conducted by Gojek and Tokopedia and their financial performance during 3 years after merger to company’s value. This research use qualitative method description analyzing from various related literature. The result show that merger have a impact to company’s value. Financial performance in this research use liquidity ratio, solvability ratio, and profitability ratio. Ratio liquidity don’t have impact to company’s value while solvability and profitability have impact to company’s value.